STUDI SOSIAL EKONOMI TRANSMIGRAN DI NAGARI LUNANG KECAMATAN LUNANG KABUPATEN PESISIR SELATAN - Putri, Siska Desnila; Juita, Erna; Nefilinda, Nefilinda (STKIP PGRI Sumbar, 2013)
This study aimed to obtain the data, process, analyze and discuss the socio economic study of migrants in Nagari Lunang Lunang Subdistrict Pesisir selatan Regency of: 1) social interaction, 2) the level of income, 3) education, 4) housing conditions. This study considered the descriptive research. The study population was a homesteader who is in Nagari Lunang Lunang Subdistrict Pesisir selatan Regency. Samples were taken with a random sampling technique with the proportion of 15% of the population in the study area, totaling 134 sample households. Guided data collection using questionnaires, statistical analysis used is descriptive by using a percentage formula. The results showed: 1) social interaction homesteader in Nagari Lunang Lunang Subdistrict Pesisir selatan Regency (100%) where between one and the other one to know one another. 2) the level of income migrants in Nagari Lunang Lunang Subdistrict Pesisir selatan Regency (54%) a week on average Rp 600000-800000, 3) education level of migrants in Nagari Lunang Lunang Subdistrict Pesisir selatan Regency (52%) had graduated from junior high school, 4) housing conditions of migrants in Nagari Lunang Lunang Subdistrict Pesisir selatan Regency (100%) are permanent.